Identifikasi Tumbuhan Obat Masyarakat Desa Lorotolus Kabupaten Malaka sebagai Media Booklet Pembelajaran Biologi - Gradiana Berek; Getrudis Wilhelmina Nau; Florentina Yasinta Sepe (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2025)
Knowledge of the use of medicinal plants by the people of Lorotolus Village, Wewiku District, Malaka Regency remains limited and is only known by a small group within the community. This study aimed to (1) identify medicinal plant species used by the community to treat human diseases, (2) determine the plant parts utilized, (3) describe the methods of preparation, and (4) develop a booklet of medicinal plants as a biology learning medium. The research employed a descriptive qualitative approach combined with research and development using a modified ADDIE model consisting of three stages: analysis, design, and development. Data were collected through interviews and documentation, then analyzed descriptively. The results identified 14 medicinal plant species, including Chromolaena odorata, Allium sativum, Piper betle, Psidium guajava, and Moringa oleifera. The most commonly used part was the leaf, while preparation methods included boiling, chewing, grinding, infusing, soaking, squeezing, and direct consumption. The developed booklet was validated by media and material experts, yielding feasibility scores of 80% and 72.5%, respectively, thus categorized as valid and feasible for use as a biology learning medium. This research highlights the importance of documenting local traditional knowledge to preserve it while utilizing it as a learning resource based on local wisdom.